Land Use Changes and Livelihood Scenarios of Rajahar VDC, Nawalparasi District, Nepal - Ghimire, Dhurba Prasad; Khatry, Sunil Babu; Rimal, Bhagawat (Ecoprint: An International Journal of Ecology, 2015)
A digital land use map of the study area Rajahar VDC at Nawalparasi district was prepared with the aid of RS/GIS for 1989 to 2013 followed by land use map analysis. The obtained image was classified as forest, agricultural, settlement, water body and religious areas for the study year 1989 to 1999 where industrial area was included as new land use category (0.07%) for 2013. The study showed that there was considerable change in forest area (-3.47%) and religious area (-0.01%). But agriculture land, settlement area and water body were increased by 2.02%, 3.66% and 1.28%, respectively. The land use change for 1989 to 2013 followed polynomial (R2: 0.6577) pattern. The identified land use change key drivers were dependent on past events and reactions of the respondents. ECOPRINT 21: 55-62, 2014 DOI: http://dx.doi.org/10.3126/eco.v21i0.11905